Influence of sulfur and selenium application on wheat growth in arsenic-contaminated soil - Huan Luo; Chipeng Zhang; Shunyuan Zhang; Wansheng Song; Han Chen (Ecotoxicology and Environmental Safety)
Wheat could become poisoned when grown in soil with high arsenic (As) content. It is worthwhile to investigate the potential use of sulfur (S) and selenium (Se) for crop protection while detoxifying heavy metal(loid)s. In this study, a pot experiment was conducted under both single and combined application of the two elements. Their effects on wheat growth were analyzed based on As distribution in subcellular tissues and the variation in physiological and biochemical indicators. Despite wheat absorbing and enriching As under S and Se application, its growth status improved. Cell wall and vacuole sequestered majority of elevated As. Phytochelatins (PCs) content increased significantly in the roots, particularly when Se was applied alone. They could chelate with As using thiol groups. Superoxide dismutase (SOD) activity was found to be considerably lower in leaves and without any discernible increase in roots. Peroxidase (POD) activity in roots/stems and/or catalase (CAT) activity in stems increased, and exerted antioxidant effects. The leaf was well protected, and its chlorophyll content significantly increased. The application of S alone had a relatively weaker effect on reducing As content in grains, but the mixed application of Se could induce an inhibitory effect.